PENGGUNAAN MEDIA SOSIAL DENGAN PENDEKATAN MODEL AIDA BAGI ROTI BUND DALAM MENINGKATKAN MINAT BELI KONSUMEN - Bunga Ega Evania; Roni Kastaman; Totok Pujianto (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The internet offers many benefits for small and medium businesses to increase the marketing of their products. One of the rapidly developing internet technologies that have the potential to encourage small and medium business marketing is social media. Roti Bund must improve its marketing strategy using social media so that it attracts consumer buying interest. This study aims to determine whether there is a positive and significant influence between the Marketing Strategy through Social Media "Instagram" in Increasing Consumer Purchase Interest of Bund Bread and applying the use of social media by referring to the AIDA Model for Roti Bund. The use of the AIDA Model is used to assist Roti Bund in maximizing the use of social media, so that Roti Bund is able to more optimally market products / services through social media. The results showed that 59.6% of consumers' buying interest was really due to the factors of attention, interest, desire and action. variable attention has the most dominant effect on the increase in consumer buying interest. So in the use of Instagram that must be optimized is the attention variable first, that is, product posts that are posted must use quality, honest and reliable visualization in the use of images and captions and must have uniqueness that differentiates bakery bund posts from other companies' posts, captions as well. must be able to arouse the desire to know more about the product for example by explaining the benefits of the product.